Contingent Factors that Influence the Accounting Information System Quality and Environmental Management Accounting Adoption among Companies in Indonesia - Aulia Tri Utama; Idrianita Anis; Juniati Gunawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Environmental management accounting has received increasing interest in recent years. However, despite increasing interest, reference concerning the current state of environmental management accounting development remain scarce. The objective of the research presented here is to extend current knowledge by investigating whether accounting information system design could be used to develop a greater understanding of environmental management accounting use by Indonesian organisations. A research framework was developed from contingency theory to identify the circumstances under which organisations were more likely to develop a sophisticated accounting information system design and ultimately to investigate its impact to environmental management accounting activities. In order to test this framework, a web-based survey of Indonesian accountants in business was conducted. This research exploits the quantitative research methodology to understand the relationship between contingent factors, which are firm size, firm age, organizational structure, uncertainty environment, and manager profile that influence accounting information system design and environmental management accouting practice among various companies in Indonesia. The survey was conducted on companies located in Jabodetabek area. 100 questionnaires were received from various companies and the finding highlights that the firm age, environment uncertainty, and manager experience significantly affect accounting information system quality and environmental management accounting practice. In light of the results, it would also be valuable to employ qualitative research methods and attempt to develop a deeper understanding as to why such lack of engagement is the case.